The Effect Of Canva-Based Audio-Visual Learning On Improving The Motivation And Academic Achievement Of Students At SDN Batioh 1 Banyuates Sampang - Rukani Rukani; Nuril Huda; Sri Utami (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This study aims to determine the effect of Canva-based audio-visual learning on the motivation and learning achievement of fifth-grade students at SDN Batioh 1 Banyuates Sampang. The background of this study is based on the low learning motivation of students, which has an impact on learning outcomes, as well as the need for learning innovations that utilize digital technology effectively and attractively. Canva-based audio-visual learning was chosen because it is able to present learning materials in a visual, interactive, and easy-to-understand manner for elementary school students. This study used a quantitative approach with an experimental method. The research design used was a pretest-posttest control group design. The research subjects were fifth-grade students at SDN Batioh 1 Banyuates Sampang, who were divided into an experimental class and a control class. Data collection techniques were carried out through learning motivation questionnaires and learning achievement tests. The data obtained were analyzed using statistical tests to determine the differences in motivation and learning achievement before and after the implementation of Canva-based audio-visual learning. The results showed that Canva-based audio-visual learning had a significant effect on increasing students' learning motivation. In addition, this learning method also had a significant effect on improving students' learning achievement compared to conventional learning. Thus, it can be concluded that Canva-based audio-visual learning is effective in increasing the motivation and learning achievement of fifth-grade students at SDN Batioh 1 Banyuates Sampang